A Small-Sized HTGR System Design for Multiple Heat Applications for Developing Countries. (26th December 2013) - Ohashi, Hirofumi; Sato, Hiroyuki; Goto, Minoru; Yan, Xing; Sumita, Junya; Tazawa, Yujiro; Nomoto, Yasunobu; Aihara, Jun; Inaba, Yoshitomo; Fukaya, Yuji; Noguchi, Hiroki; Imai, Yoshiyuki; et al.
Abstract : Japan Atomic Energy Agency has conducted a conceptual design of a 50 MWt small-sized high temperature gas cooled reactor (HTGR) for multiple heat applications, named HTR50S, with the reactor outlet coolant temperature of 750°C and 900°C. It is first-of-a-kind of the commercial plant or a demonstration plant of a small-sized HTGR system to be deployed in developing countries in the 2020s. The design concept of HTR50S is to satisfy the user requirements for multipurpose heat applications such as the district heating and process heat supply based on the steam turbine system and the demonstration of the power generation by helium gas turbine and the hydrogen production using the water splitting iodine-sulfur process, to upgrade its performance compared to that of HTTR without significant R&D utilizing the knowledge obtained by the HTTR design and operation, and to fulfill the high level of safety by utilizing the inherent features of HTGR and a passive decay heat removal system. The evaluation of technical feasibility shows that all design targets were satisfied by the design of each system and the preliminary safety analysis. This paper describes the conceptual design and the preliminary safety analysis of HTR50S.